Answer:
x = 5
y = 2
Explanation:
In this question, you will have to use one of the equations to find the value of x in terms of y and substitute it in the other equation or vice versa.
y = 2x - 8
x - y = 3
Use the second equation to find the value of x in terms of y.
x - y = 3
x = y + 3
Now that we found that, we can substitute it in the other equation.
y = 2 (y + 3) - 8
y = 2y + 6 -8
y = 2y -2
y + 2 = 2y
y = 2
Now that we got y we can substitute the value in any of the equations to find x.
x - 2 = 3
x = 5